Effectiveness of Interventions to Reduce Sedentary Behaviour in People with Chronic Obstructive Pulmonary Disease: A Systematic Review of Randomised Controlled Trials - Stefanie Harding; Alan Richardson; Angela Glynn; Luke Hodgson (COPD)
Background Chronic obstructive pulmonary disease (COPD) affects over 300 million people and is the third leading cause of death. People with COPD spend a large amount of their day sedentary, which is associated with reduced life expectancy.Methods A systematic search was conducted across electronic databases, including Medline, CINAHL, PsycINFO, and Cochrane Library. Due to the heterogeneity of study design and siting of the activity monitor, a narrative synthesis was conducted.Results 1086 studies were identified; six met inclusion criteria, and two reported a decreased sedentary time. Nordic walking reduced sedentary time by 128 minutes/day compared to baseline, significantly more than the control group (p < 0.01). Another study using a behaviour change intervention reduced sedentary behaviour by 64 minutes/day compared to baseline, significantly more than the control group (p = 0.018). Both studies were conducted for over 12 weeks, with a multi-modal approach incorporating behaviour change techniques, goal setting, education, self-monitoring and feedback. No studies focusing on reducing sedentary behaviour alone reported significant changes.Conclusions Few interventional studies have focused on reducing sedentary behaviour in people with COPD. Interventions that have effectively reduced sedentary time primarily focused on physical activity and adopted a multi-modal strategy. This suggests that future interventions could consider a multi-modal approach, which includes behaviour change and the incorporation of enjoyable light physical activities into daily living. We cannot conclude from the available evidence that solely targeting sedentary time will reduce sedentary behaviour. Longer interventions may reduce sedentary behaviour, but there is a lack of studies on both short- and long-term approaches.PROSPERO registration number CRD 42024510434.